Zen teen : 40 ways to stay calm when life gets stressful - Richardson, Tanya Carroll, 1974- (Seal Press, 2018)
In the last decade, studies have reported a drastic rise in teens who experience anxiety, panic, and an inability to cope with the pressures of daily life. As mental health challenges become less stigmatized, young people are more likely than ever before to know how to identify their feelings and ask for help. Even celebrity teen icons like Selena Gomez are "coming out" as anxiety sufferers. Zen Teen addresses this epidemic with powerful coping mechanisms and creative tools-including two fun quizzes, tons of engaging exercises and a cool playlist-designed for the teenage mind.